The body, sex, and politics: consequences of the use of sexual education as a campaign issue in Costa Rica - Sánchez Hernández, Carolina (2022)
This text reflects on the long-term effects of a political campaign that dealt with issues related to people’s bodies and sexuality. The purpose of the article is to analyze the way in which a populist discussion for electoral reasons during the 2018 campaign in Costa Rica led to legal precedents that marked a setback in the underage people’s right of sex education. A documentary review and a descriptive analysis of media events and Constitutional Chamber’s statements on the subject are proposed. As a result, a series of consequences are evident in restricting people's access to sexual citizenship and violating their possibilities to access information, react to violence, or prevent life-threatening situations which is significantly limiting the exercise of their human rights.